1987
DOI: 10.1073/pnas.84.15.5501
|View full text |Cite
|
Sign up to set email alerts
|

Simultaneous measurement of hormone release and secretagogue binding by individual pituitary cells.

Abstract: The quantitative relationship between receptor binding and hormone secretion at the single-cell level was investigated in the present study by combining a reverse hemolytic plaque assay for measurement of luteinizing hormone (LH) secretion from individual pituitary cells with an autoradiographic assay of l251-labeled gonadotropin-releasing hormone (GnRH) agonist binding to the same cells. In the plaque assay, LH secretion induces complement-mediated lysis of the LH-antibody-coated erythrocytes around the gonad… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
9
0

Year Published

1988
1988
2010
2010

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 18 publications
(11 citation statements)
references
References 21 publications
2
9
0
Order By: Relevance
“…Our finding that Bax is expressed predominantly in the gonadotrope combined with the fact that the gonadotrope is the primary pituitary target of GnRH [38, 39]support the hypothesis that GnRH inhibits apoptosis of pituitary gonadotropes by suppressing Bax expression. Because GnRH acts on the gonadotrope to stimulate gonadotropin secretion as well as cell proliferation [40, 41], the concurrent stimulation of cell proliferation and cell survival of gonadotropes at estrus may be accounted for by GnRH, a multifunctional hormone that regulates all events of cell proliferation, apoptotic cell death, and hormone secretion.…”
Section: Discussionsupporting
confidence: 55%
“…Our finding that Bax is expressed predominantly in the gonadotrope combined with the fact that the gonadotrope is the primary pituitary target of GnRH [38, 39]support the hypothesis that GnRH inhibits apoptosis of pituitary gonadotropes by suppressing Bax expression. Because GnRH acts on the gonadotrope to stimulate gonadotropin secretion as well as cell proliferation [40, 41], the concurrent stimulation of cell proliferation and cell survival of gonadotropes at estrus may be accounted for by GnRH, a multifunctional hormone that regulates all events of cell proliferation, apoptotic cell death, and hormone secretion.…”
Section: Discussionsupporting
confidence: 55%
“…The gonadal sex steroids are part of a negative feedback pathway inhibiting LH and FSH release at least partially via inhibition of GnRH release (6,12,23,28,37). Previous work has suggested that enhanced sensitivity of GnRH neurons to the sex steroid negative feedback occurring specifically in response to the short photoperiods of winter may be one cause of winter suppression of fertility in seasonally reproducing mammals (14,25,32).…”
Section: Discussionmentioning
confidence: 97%
“…This assay permits assessment of the activity of individual hormone-secreting cells (Smith & Neill 1987). Beta cells were exposed to glucose (1·4-16·5 mM) plus insulin antibody for 2 h, then guinea pig complement for 30 min.…”
Section: Reverse Hemolytic Plaque Assay (Rhpa) For Beta Cellsmentioning
confidence: 99%